DA MATEMÁTICA NATIVA PRESENTE NO PENSAMENTO DAS AUTORIDADES TRADICIONAIS DA TRIBU UMBUNDO COM RESPEITO A FORMA DO ONDJANGO NO CUITO/BIÉ-ANGOLA PARA PROBLEMAS ISOPERIMÉTRICOS DA GEOMETRIA PLANA. - CASSELA, Ezequias Adolfo Domingas (ERAS: European Review of Artistic Studies, 2020)
This article presents an approach related to the thawing of native and intuitive mathematics frozen in the thinking of the traditional authorities of the municipality of Cuito whose mathematical interpretation process suggests a motivational and significant activity in the teaching-learning of flat geometry, based on the student's context. The mathematical result presented allows a cultural decolinization leading to a possible understanding on the part of the student that Mathematics is not something completely foreign imported from outside Africa. The mathematical ideas extracted from an informal conversation with the traditional authorities of the municipality of Cuito can contribute to the optimization of the Teaching-Learning Process in the subject of Flat Geometry.